Judicial Review of Administrative Action at National Level under the EU Charter of Fundamental Rights and General Principles of EU Law - Mihaela Vrabie (Central European Public Administration Review)
This article aims to determine when the national authorities have the obligation to comply with EU fundamental rights, in the framework of administrative procedures carried out in the EU Member States. It also aims to determine the legal remedies available at national level in the context of judicial review in case of violation, by the national authorities, of EU fundamental rights guaranteed by the Charter of Fundamental Rights of the EU or as general principles of EU law. To this end, this study explains the impact of the legally binding EU Charter on public administration of the Member States and the field of application of the EU Charter at national level. The article also deals with the distinction between EU fundamental rights as primary EU law guaranteed by the EU Charter and EU fundamental rights as general principles of EU law. With reference to the judicial remedies available to national courts, the study outlines the effects of EU law (primacy of EU law, direct effect, direct application) in relation to the EU fundamental rights and the measures that can be adopted by the national courts when the action of the national administrative authorities is not compatible with EU fundamental rights. Finally, the article presents the most important findings concerning judicial protection of EU fundamental rights at the national level, especially from the perspective of the right to an effective remedy and to a fair trial stipulated by Article 47 of the EU Charter.